2018
DOI: 10.1039/c8cp03631d
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical tuning of capacitive response of graphene oxide

Abstract: The increasing energy demands of modern society require a deep understanding of the properties of energy storage materials, as well as the tuning of their performance. We show that the capacitance of graphene oxide (GO) can be precisely tuned using a simple electrochemical reduction route. In situ resistance measurements, in combination with cyclic voltammetry measurements and Raman spectroscopy, have shown that upon reduction GO is irreversibly deoxygenated, which is further accompanied by structural ordering… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
(81 reference statements)
2
9
0
Order By: Relevance
“…The band associated with defects in ZnO (e.g., oxygen vacancies) at 580 cm −1 indicates the hybridization of ZnO with GO and shows that at a higher GO content (i.e., 10 mg L −1 ), the hybridization reaches a limitation as it did not change in location or full width half maximum. The peaks corresponding to GO indicate that the I D /I G ratio is relatively higher at −1.0 V than lower applied deposition potentials, which is attributed to an increased reduction degree [23,28,47,[53][54][55].…”
Section: The Chronoamperometric Curves Inmentioning
confidence: 99%
“…The band associated with defects in ZnO (e.g., oxygen vacancies) at 580 cm −1 indicates the hybridization of ZnO with GO and shows that at a higher GO content (i.e., 10 mg L −1 ), the hybridization reaches a limitation as it did not change in location or full width half maximum. The peaks corresponding to GO indicate that the I D /I G ratio is relatively higher at −1.0 V than lower applied deposition potentials, which is attributed to an increased reduction degree [23,28,47,[53][54][55].…”
Section: The Chronoamperometric Curves Inmentioning
confidence: 99%
“…1 (bottom panel) it can be observed that the CIFs are significantly lower when conductive additive is used. As previously explained [19] this is not a negative effect of the conductive carbon added to the GO layer, but the consequence of higher initial GO capacitances due to a higher conductivity of the GO/conductive component film. Namely, we measured the initial specific capacitances (i.e.…”
Section: (Top Panel)mentioning
confidence: 53%
“…The GO sample used in this work possesses high concentration of oxygen functional groups (C:O ratio close to 1) and a small concentration of heteroatoms (S and N). Due to high oxidation degree it is non conductive, as known for GO [19,23]. It undergoes irreversible electrochemical reduction, which is observed under both potentiodynamic and potentiostatic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current value was improved to 23 µ A for rGO/SPCEs owing to the electrochemical reduction process that removed a considerable number of oxygenated functional groups. Studies have shown that electrochemical reduction with precise control over the reduction potential and time [11,12] allows reproducibility of rGO for use in electrochemical devices [13]. We found that IgG/rGO/SPCEs achieved the highest current value of 73 µA, which could be due to the semiconductive nature of protein in dry and wet states [14].…”
Section: Linear Sweep Voltammetry For Bare Spces Go/spces Rgo/spces and Igg/rgo/spcesmentioning
confidence: 76%